Erak's ransom - Flanagan, John (John Anthony) (London : Corgi Yearling, 2011)
On a mission to pay the ransom of a new ally, apprentice Will and his friends find themselves in a desert wasteland awash with enemies.
Horn Book
Wilson's Junior High School
Horn Book, October 2010
Wilson's Junior High School, October 2010
6.1
5-8.
Keywords: Apprentices -- Juvenile fiction; Deserts -- Juvenile fiction; Apprentices -- Fiction; Deserts -- Fiction; Fantasy; War -- Fiction; Apprentices -- Fiction; Deserts -- Fiction; War stories; Fantastic fiction; Fantastic fiction; War stories